An algorithm of the development of an author’s educational program - Bachiеva L. (Problems of Engineer-Pedagogical Education, 2019)
The article presents an algorithm for developing an author's educational program. The analysis of the essence of the "author's educational program" concept makes it possible to determine that in its interpretation, researchers do not take into account the main indicators that characterize the result and product of intellectual activity such as novelty, relevance and practical significance, do not highlight the importance of presenting it as an object of copyright. On the basis of the results of the analysis of literary sources and personal experience, the author's definition of the concept "author's educational program" is formulated. In order to simplify the process of creating an author's educational program, we have developed and presented an algorithm. Its peculiarity is a detailed verbal instruction for the steps that should be taken to carry out activities and a description of the results that are expected to be obtained after each of them. Stages of the program are defined in accordance with the logic of scientific research. Thus, the algorithm of the author's program development is considered to be a process of realization of prognostic, informational-analytical, modeling-designing, experimentalmeasuring and evaluation-reflexive stages of activity. The goal and steps of each stage of creating an author's educational program are defined: prognostic (determining the target audience and its educational needs); informational-analytical (collection and analysis of content of materials of similar curricula, existing pedagogical theory and practical activity of educational institutions, selection, detailed analysis, evaluation of scientific information of official programs, program and methodological materials, etc.); modeling-designing (definition of the generalized purpose and name of the course, formulation of tasks, selection of the required content and its description, establishment of the number of types of classes, definition of didactic components (principles, methods, forms and means of teaching and learning), analysis of the resource base of the educational institution for the implementation of the course, creation of a system of controlling the acquisition of materials; preparation of methodological and didactic materials); experimental-measuring (design of a teaching methodology with regard to the program; presentation of the results of experimental teaching); evaluation-reflexive stage (clarification of social demand, analysis of the educational institution's capacity for the implementation of the program, registration of the copyright of the program).